2017
DOI: 10.1016/j.brat.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Pavlovian disgust conditioning as a model for contamination-based OCD: Evidence from an analogue study

Abstract: Pavlovian fear conditioning provides a model for anxiety-related disorders, including obsessive-compulsive disorder (OCD). However, disgust is the predominant emotional response to contamination, which is a common theme in OCD. The present study sought to identify disgust conditioning abnormalities that may underlie excessive contamination concerns relevant to OCD. Individuals high and low in contamination concern (HCC, n = 32; LCC, n = 30) completed an associative learning task in which one neutral face (cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 59 publications
4
19
0
Order By: Relevance
“…One hundred and sixty-two lay people were tested using Padua's inventory contamination subscale (PI-C, Sanavio et al, 1998), to identify people with low and high contamination-related concerns. In line with other studies (Armstrong, 2017, Deacon & Maack, 2009, Deacon & Olatunji, 2007. Conform to Armstrong's work (2016), individuals with scores greater than 13 (77 : 47.53% of the sample tested) were considered eligible for the group with high concerns about dirt and contamination (HDCC) and individuals with scores below 7 (42 : 27.92% of the sample tested) were considered eligible for the group with low concerns regarding dirt and contamination (LDCC).…”
Section: Participantssupporting
confidence: 93%
“…One hundred and sixty-two lay people were tested using Padua's inventory contamination subscale (PI-C, Sanavio et al, 1998), to identify people with low and high contamination-related concerns. In line with other studies (Armstrong, 2017, Deacon & Maack, 2009, Deacon & Olatunji, 2007. Conform to Armstrong's work (2016), individuals with scores greater than 13 (77 : 47.53% of the sample tested) were considered eligible for the group with high concerns about dirt and contamination (HDCC) and individuals with scores below 7 (42 : 27.92% of the sample tested) were considered eligible for the group with low concerns regarding dirt and contamination (LDCC).…”
Section: Participantssupporting
confidence: 93%
“…Nevertheless, this outcome would likely be different if the fear conditioning and extinction paradigm consisted of common themes relevant to OCD. For example, Armstrong and Olatunji (2017) used an associative learning task that showed a neutral face that was followed by a disgusting image (unconditioned stimulus) and a neutral face that was not paired with a disgusting image (CS-) and found that individuals with high and low contamination concerns did not differ in discriminant responding. However, those with high contamination concerns, who exhibited symptoms consistent with individuals with OCD, reported more considerable disgust to the CS+, and their unconditioned stimulus expectancy during the CS+ was resistant to extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Among the examples that were mentioned repeatedly in relevant studies are decomposed food (such as rotten meat or food with mold), objects on which dirt can be observed, and objects the person considers can transmit contamination because they were or are in contact with objects, people, or places infected or dirty (Breiter et al, 1996;Rachman, 2004;Armstrong and Olatunji, 2017;Mathes et al, 2019). Based on this, the four aversive stimuli developed in this project were a sealed plastic bag (full of garbage), bread with mold, rotten meat, and sports shoes with dirt on their surface.…”
Section: Methodsmentioning
confidence: 99%
“…From the results found in the literature review four AR stimuli were developed (Breiter et al, 1996;Rachman, 2004;Armstrong and Olatunji, 2017;Mathes et al, 2019). These stimuli aimed at causing the emotions experienced by the people who suffer from cleaning OCD.…”
Section: Ar Stimuli Developmentmentioning
confidence: 99%
See 1 more Smart Citation